42 Gender Differences in Response to Transcatheter Aortic Valve Implantation in Patients with Severe Aortic Stenosis Assessed by Feature Tracking. (3rd June 2016) - Foley, James RJ; Dobson, Laura E; Musa, Tarique A; Fairbairn, Timothy A; Uddin, Akhlaque; Swoboda, Peter P; Garg, Pankaj; Fent, Graham J; Haaf, Philip; Malkin, Christopher J; Blackman, Daniel J; Plein, Sven; et al.
Abstract : Introduction: Aortic stenosis (AS) results in left ventricular hypertrophy, myocyte dysfunction and fibrosis as a physiological response to excessive afterload. Transcatheter Aortic Valve implantation (TAVI) is an effective treatment for severe AS, however controversy exists whether gender predisposes to improved myocardial function post procedure. Feature-tracking cardiovascular magnetic resonance (FT-CMR) is a novel method for quantification of myocardial strain and strain rate that can identify subtle changes in left ventricular (LV) mechanics prior to overt changes in LV ejection fraction (EF). Our aim was to compare the acute impact of TAVI on LV function between males and females defined by strain measurements. Methods: 59 patients, 34 males and 25 females matched for age (78.4 ± 7.19 years vs 78.8 ± 9.7 years p = 0.876), EuroSCORE II (5.19 ± 4.33% vs 4.26 ± 2.99% p = 0.788) and presence of baseline myocardial fibrosis (p = 0.829) with severe, symptomatic AS were prospectively enrolled prior to TAVI. All patients underwent an identical 1.5T CMR protocol (Intera or Ingenia, Phillips Healthcare, Best, The Netherlands) at baseline and at a median of 4 days following TAVI. Endocardial and epicardial borders were traced manually on the end-diastolic slice, then strain and strain rate measurements were obtained using commercially available post-processing software (CVI42, Circle Cardiovascular Imaging, Calgary, Alberta, Canada). Results: TAVI was associated with a significant and comparable reduction in peak aortic pressure gradient and LV mass index in both men and women (Table 1 ). There was no significant difference in extent of pressure drop (p = 0.374) or extent of regression of LV mass index (p = 0.095) between men and women. There was no significant change in left ventricular end diastolic volume indexed (LVEDVI) or LVEF observed acutely following TAVI, in men or women (Table 1 ). Longitudinal strain (Ell ), circumferential strain (Ecc ) and circumferential strain rate (SRcc ) did not change significantly in men or women (Table 2 ). However, TAVI was associated with a significant increase in longitudinal strain rate (SRll ) in males (p = 0.012) that was not observed in females (p = 0.184) (Table 2 ). Conclusion: TAVI was associated with structural reverse remodelling that was comparable between males and females. Functional recovery in LV mechanics following TAVI may occur earlier in males than in females, although this may reflect the higher LVMI that men have at baseline prior to TAVI.